An approach to the cross-cultural and intercultural communication in the Nigerian government-linked companies - Muhamad Fazil, Ahmad; Rukayat, A. Shittu (2020)
Culture and communication are two commonly dependent problems. Individuals with different cultures can communicate effectively only if their cultural differences are succeeded and the eventual communication barriers overcome. It is well accepted today that cultural differences can seriously impact the activities in business institutions. With globalization and international business, effective cross-cultural communication is required at the workplace to ensure success, especially in carried out corporate social responsibility projects as a team. This study aims to examine the relationship between cross culture corporate social responsibility projects (cultural factors) and intercultural communication (IC) in Nigerian government-linked companies. It intends to show that effective communication may occur when interacting people understand and accept their cultural differences.